Medical treatment of patients with cardiovascular diseases during the first year after hospitalization for COVID-19 - N. P. Kutishenko; M. M. Lukyanov; S. Yu. Martsevich; A. A. Pulin; E. Yu. Andreenko; V. P. Voronina; V. A. Dindikova; N. A. Dmitrieva; M. M. Kudryavtseva; O. V. Lerman; A. N. Makoveeva; E. Yu. Okshina; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the medical treatment of patients with cardiovascular disease (CVD) during the first year of follow-up after hospitalization for coronavirus disease 2019 (COVID-19) in a prospective registry.Material and methods. The material for the study was obtained from the database of the TARGET-VIP inhospital registry. The registry included 1130 people. Of 863 patients discharged from the hospital with a diagnosis of COVID-19, 473 (548%) patients with CVD were selected, and 31 (40,8%) patients were selected from 76 patients in whom the diagnosis of COVID-19 was not confirmed with CVD.Results. At the stage of discharge from the hospital, the quality of therapy for CVD was insufficient on average, the frequency of proper prescriptions was 59,5%. During the first year, there was a significant trend towards a decrease in the prevalence of antihypertensive therapy for hypertension (p=0,018), anticoagulants for atrial fibrillation (p<0,001) and an increase in prescribing angiotensinconverting enzyme inhibitors/angiotensin receptor blockers for heart failure (p=0,037). The average prevalence of prescribing proper cardiovascular pharmacotherapy after 30-60 days and 6 months of follow-up was significantly less than at discharge from the hospital. In both groups of patients, when comparing the average frequency of compliance with proper prescriptions at all follow-up periods, as well as when comparing these indicators between groups, no significant differences were found, with the exception of the stage of 30-60 days after discharge from the hospital (p=0,009).Conclusion. In the TARGET-VIP registry after discharge from the hospital, the prevalence of proper appointments for CVD was insufficient. During the first year of observation, patients with CVD showed a significant decrease in the frequency of proper prescription of antihypertensive therapy for hypertension and anticoagulants for atrial fibrillation. When comparing groups of patients with confirmed and non-confirmed COVID-19, a higher average rate of adherence to proper prescriptions was found in patients with confirmed COVID-19. However, significant differences were found only 30-60 days after discharge.